Scale-up of microstructured Fischer–Tropsch reactors – status and perspectives. (June 2022) - Pfeifer, Peter; Schmidt, Sebastian; Betzner, Florian; Kollmann, Max; Loewert, Marcel; Böltken, Tim; Piermartini, Paolo
Abstract : Recently, INERATEC GmbH has been working on different projects on the upscaling and validation of compact microstructured Fischer–Tropsch reactors for producing carbon-neutral liquid fuels from enhanced biomass gasification (Biomass-to-Liquid) and from hydrogen from renewable power (Power-to-Liquid). In this contribution, Fischer–Tropsch reactors in different configuration that is, serial and parallel operation, based on reaction heat removal by pressurized steam generation are investigated for different applications. The feasibility of modularization even under the constraints of load flexibility is demonstrated. Furthermore, plate sizes suitable for 2 barrel-per-day (total hydrocarbon product) and larger reactors, are experimentally validated, which means that a scale-up by a factor of larger than 5000 has been progressed from lab. Power-to-X (PtX) plants using these reactors have been built in the size of up to 1 MW(el) electrolysis size for commercial industrial environment. 1.25 MW(el) reactors are the current basis for further plant scale-up applying modularization. The produced fuels can serve as long-term energy storage of renewable power, as a sustainable alternative to fossil fuels and for chemical applications.